PANDANGAN HIDUP PEREMPUAN MINANGKABAU YANG TERCERMIN DALAM NOVEL PEREMPUAN BATIH KARYA A.R RIZAL - Kalsum, Yuli Sri; Effendy, Chairil; Nadeak, Parlindungan (Universitas Tanjungpura, 2023)
This research is inspired by the importance of investigating women's perspectives on life in novels. A.r. Rizal's Perempuan Batih reflects the standpoint of Minangkabau women on life, which is the central issue of this study. The purpose of this study is to describe the discussed problems, while the benefits of this research are that it can enrich the development of linguistics and literature, particularly in the field of sociology of literature studies, and that it can be used as a reference in teaching Indonesian language and literature. This study employs a qualitative descriptive research strategy and a literary sociology methodology. Based on the position of women in Minangkabau society, the novel's analysis reveals the following Minangkabau women's perspectives on life: 1) The view of women as the oldest pillar of the gadang house, 2) The view of women as holder of the key to the heirloom, and 3) A guide to heaven. The Minangkabau women's perspective on life, which is founded on their unity, consists of the following: 1) A view of equality, 2) A view of feeling and checking, and 3) A view of one accord. Based on their work ethic, Minangkabau women have the following perspectives on life: 1) View of life, 2) View of life toward labour, and 3) View of life on time. The outcomes of this study are referred to as a 2013 curriculum implementation plan for studying Indonesian at the 12th-grade level.